Association of patellofemoral osteoarthritis on patient-reported outcomes after medial unicompartmental knee arthroplasty: a retrospective cohort study - Jonathan Winther Olsen; Christian Bredgaard Jensen; Kristine Ifigenia Bunyoz; Anders Flygenring Bagge; Kirill Gromov; Anders Troelsen (Acta Orthopaedica)
Background and purpose: In contemporary medial unicompartmental knee arthroplasty (mUKA), non-lateral patellofemoral osteoarthritis (PFOA) is not considered a contraindication. However, we still lack knowledge on the association of PFOA severity on patient reported outcome measures (PROMs) after mUKA. We aimed to examine the association between PFOA severity and PROM-score changes after mUKA. Methods: We included 549 mobile-bearing mUKAs. PFOA was graded intraoperatively as 0 = normal cartilage, 1–2 = superficial changes or < 50% of depth, and 3–4 = changes of > 50% of depth or to the bone, using the International Cartilage Repair Society (ICRS) cartilage lesion classification system. All patients completed the Oxford Knee Score (OKS), Activity and Participation Questionnaire (APQ), and Forgotten Joint Score (FJS), preoperatively and 3, 12, and 24 months postoperatively. PROM changes were compared using linear regression models adjusted for sex, age, body mass index, and preoperative PROM score. Results: We found no significant differences in OKS, FJS, and APQ change when comparing group 3–4 with group 0 at any follow-up. When comparing group 1–2 with 0 we found a statistical but not clinical significantly higher change in OKS scores at 24-month follow-up (2.5, 95% confidence interval [CI] 0.36–4.6) and in APQ scores at 24-month follow-up (10.6, CI 1.2–20.0) in favor of group 1–2. Conclusion: Severe PFOA, excluding severe lateral facet PFOA, had no negative association on PROM score development following mobile-bearing mUKA.